Recent brachiopods from the Tonga Islands, SW Pacific: taxonomy and biogeography - Bitner, M. A. (Rivista Italiana di Paleontologia e stratigrafia, 2019)
Twenty species of Recent brachiopods belonging to the genera Neoancistrocrania, Basiliola, Basiliolella, Dyscolia, Abyssothyris, Xenobrochus, Terebratulina, Fallax, Septicollarina, Frenulina, Amphithyris, Annuloplatidia, Leptothyrella, Dallina, Campages, Thecidellina and Minutella have been identified in the material collected during the French cruise Bordau 2 to the Tonga Islands, South-West Pacific. Apart from Frenulina sanguinolenta all species represent the first records for the Tonga Islands. The investigated brachiopod fauna shows the greatest affinity to that from Fiji and New Caledonia, having 16 and 12 species in common, respectively. Although less affinity is observed with the New Zealand fauna, there are two species, Terebratulina australis and Amphithyris buckmani reported so far only from New Zealand, Fiji and Tonga. The biodiversity of brachiopods in Tonga is similar to that in Fiji but half as great as that in New Caledonia and New Zealand regions and much higher than in French Polynesia.